Critical chloride content in reinforced concrete — An updated review considering Chinese experience. (March 2019) - Cao, Yin; Gehlen, Christoph; Angst, Ueli; Wang, Ling; Wang, Zhendi; Yao, Yan
Abstract: The critical chloride content ( C crit ) of reinforcement corrosion in concrete is of great importance for the condition assessment of existing structures and for the service life design of new structures in chloride exposure environments. Here, we review the extensive body of literature on C crit published in Chinese since the 1960s. In agreement with earlier reviews considering European and North American literature, we find that C crit scatters widely and cannot be predicted on the basis of parameters such as w/b ratio, binder type, steel surface condition, etc. It appears that the stress state of the reinforcing steel may play a more important role than generally assumed. On the basis of this review, complementing earlier reviews, we conclude that the state-of-the-art on C crit has advanced negligibly over the last decades. The time is now to change the way corrosion initiation in concrete is scientifically addressed. Recommendations for further work are made.